42.7k views
2 votes
2) −4 + n/3= −4 solve the equation

2 Answers

6 votes
The person above me is correct I checked it :)
5 votes

Answer: n=−6

Step-by-step explanation: Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

2-4+n/3-(-4)=0

simplify n/3

(-2+n/3)- -4=0

Rewrite the whole as a fraction using 3 as the denominator :

-2 • 3

-2 = -2/1 = -2X3/3

Equivalent fraction : The fraction thus generated looks different but has the same value as the whole

Common denominator : The equivalent fraction and the other fraction involved in the calculation share the same denominator

-2 • 3 + n /3=n-6/3

n+6 = 0

Subtract 6 from both sides of the equation :

n = -6

User AvcS
by
5.0k points